SPIRIT “AL-MA’UN” DARI TEOLOGI KE GERAKAN: MEMBACA PERKEMBANGAN PENDIDIKAN DAN POLITIK DI MUHAMMADIYAH - Selamet, Sopaat Rahmat; Muhammad, Afif (FASTABIQ: JURNAL STUDI ISLAM, 2023)
The of Muhammadiyah in the city of Garut in the early 20th century made an important contribution to the development of education and national politics. This was played by the merchants of Muhammadiyah Pasar Baru. Purpose, to understand the internalization of the Al-Ma’un Theological Spirit among Muhammadiyah Garut merchants in developing education and Politics in 1921-1945. Method, the reseach uses the historical reseach with a qualitative approach, namely analyzing document sources (texts), artifacts, and conducting analytical descriptive of the sources. As result, Muhammadiyah merchants internalized the spirit of Al-Maun theologi taught by KH Ahmad Dahlan as a result of direct interaction with KH Ahmad Dahlan and his students. Muhamamdiyah merchants in the city of Garut apply the spirit of Al-Maun, one of which is by developing education for indigenous people in Garut and more broadly being active in politics to realize national independence. Keywords: Economy; Islamic Movement; Education; Theology